(untitled) (Entrepreneurship Journal for Finance and Business, 2025)
Renewable Energy and Its Role in Maintaining Climate Balance The intensity of global climate challenges is increasing, prompting a focus on renewable energy production to achieve the necessary climate balance. Reports from global institutions and specialized organizations indicate that greenhouse gas emissions need to be reduced by nearly half by 2030 to avoid the worst effects of climate change and reach net-zero emissions by 2050. Global reports highlight that a significant portion of greenhouse gases surrounding the Earth, which trap the Sun’s heat, is generated through energy production by burning fossil fuels to produce electricity and heat. Fossil fuels, such as coal, oil, and gas, are by far the largest contributors to global climate change, accounting for more than 75% of global greenhouse gas emissions and nearly 90% of all carbon dioxide emissions. The role of renewable energy sources (abundantly available around us through the sun, wind, water, waste, and geothermal energy) stands out due to their natural availability. These sources emit little to no greenhouse gases or pollutants, making them a critical component in combating climate change.